Health Status and Disinfection Prior to Grafting Affect the Phenolic Profile of Grapevine Hetero-Grafts and Grafting Yield - Saša Krošelj; Maja Mikulic-Petkovsek; Domen Kjuder; Anja Pavlin; Matevž Likar; Andreja Škvarč; Katerina Biniari; Denis Rusjan (Plants)
Grapevine trunk disease (GTD) is a major threat to grapevine propagation, severely affecting the growth and development of young vines. As one of the most destructive plant diseases in the world, GTD spreads easily through propagation material and threatens the sustainability of vineyards. While effective, biologically friendly treatments remain unavailable. This study investigated the graft yield, the growth potential of grapevine hetero-grafts, and phenolic responses focusing on (i) GTD scion health status (healthy—HLT; asymptomatic—ASYM; symptomatic—SYM) and (ii) disinfection methods. Grafting with HLT scions achieved the highest yield rates, particularly with Serenade® ASO (75%) and BioAction ES (79%), while infected scions showed lower yields. The growth potential of the scions was not affected by the disinfection method or the health status of the scions. Phenolic composition varied between scions, graft callus, rootstock canes, and roots, with scion health status strongly influencing most metabolites. Higher levels of flavanols were observed in HLT scions treated with BioAction ES and Serenade® ASO, with these treatments resulting in 1.6 and 1.5 times higher procyanidin dimer levels, respectively, compared to Beltanol. Flavanols and stilbenes were lower in the callus tissue of grafts with healthy scions compared to infected scions. Rootstock also showed higher levels of catechin and procyanidin dimers in grafts with HLT scions. These results indicate that the health status of scion GTD and the disinfection methods significantly influence the graft yield and phenolic composition, providing valuable insights for GTD management.